P122 Contribution of integrated somatosensory and auditory inputs to the cortical response evoked by transcranial magnetic stimulation: A sham TMS-EEG study - Conde, V.; Akopian, I.; Tomasevic, L.; Stanek, K.; Bergmann, T.O.; Siebner, H.R. (Clinical neurophysiology, 2017)
Transcranial Magnetic Stimulation (TMS) can effectively stimulate non-invasively the human cortex. The TMS-evoked cortical response can be recorded with electroencephalography (EEG). However, TMS also stimulates our senses by stimulating peripheral trigeminal nerve fibers and creating a loud click. This implies that the TMS-evoked EEG response not only reflects neural activity induced by transcranial excitations of neurons but also neural activity due to somatosensory and auditory stimulation. To characterize the contribution of multisensory peripheral stimulation to TMS-evoked cortical potentials (TEPs), we recorded the evoked EEG response caused by a somato-auditory sham condition which mimicked real TMS. In 20 healthy individuals, TMS was delivered with a figure-of-eight coil over two target sites (posterior parietal cortex and superior frontal gyrus) using two different coil orientations, perpendicular or parallel to sulcus orientation. The sham condition comprised of simultaneous somatosensory and auditory stimulation over the same hotspots as for real TMS. Somatosensory stimulation was achieved via cutaneous electrical stimulation of the scalp, while the TMS coil was used for auditory stimulation ensuring no electric field was induced in the brain by physically separating the coil from the scalp. EEG was acquired with a 61-channel TMS-compatible EEG system. While the early cortical potentials evoked by real or sham TMS differed, TEPs were closely matched in terms of shape and spatial distribution for late components of the evoked EEG responses 70–200ms after the TMS pulse (see Fig. 1 [Display omitted] ). This was also the case for the N100 which has been commonly attributed to TMS-induced cortical inhibition. The resemblance of the EEG responses evoked by real and sham TMS challenges the notion that TEPs are mainly reflecting transcranial excitation of cortical neurons. This work has been funded by the Novo Nordisk Foundation Interdisciplinary Synergy Program 2014 [“Biophysically adjusted state-informed cortex stimulation (BASICS); Grant No. NNF14OC0011413].